(untitled) (The Planet, 2023)
Introduction:Diarrhea is one of the main causes of childhood disability and death worldwide, resulting in 5-10 million deaths annually. It is a major public health problem in developing countries like Bangladesh. It was observed that probiotics alleviated diarrhea in 3-4 days.Methods and materials:This study examined the effects of zinc and probiotics in combination for the management of acute diarrhea in children. 50 children were divided into two groups, where Group I received a combination of zinc and probiotics and Group II received probiotics alone. Result: Group I had a mean age of 18.22±11.78 months and 60.0% of patients were male, with a mean weight of 10.92±3.6 kg. 26.0% had mild malnutrition and 28.0% had fever. 64.0% had a volume of stool/purging 7-13, and the mean hospital stay was 3.46±1.02. Group II had a mean age of 12.66±7.87 months and 44.0% were male, with a mean weight of 9.26±2 kg. 24.0% had mild malnutrition and 24.0% had fever. 72.0% had a volume of stool/purging 7-13, and the mean hospital stay was 3.99±1.13. Overall, 44.0% of patients had a number of vomitus <5 and 90.0% had liquid consistency of stool.Conclusion: Zinc and probiotic therapy together is more effective in treating diarrhoea and vomiting in children than probiotic therapy alone. Clinical pharmacist interventions can reduce the emergence and severity of this disease, and education and counseling of mothers is essential for effective management.